Integrative taxonomy of Haemaphysalis (Acari: Ixodidae) from the Western Ghats, India: Morphological and molecular characterization and implications - K.R. Reshma; K. Prakasan; R. Aswathi; A.P. Ranjith (PLoS ONE, 2026)
Haemaphysalis ticks (Ixodidae) are important vectors of pathogens affecting humans and animals, yet their genetic diversity and subgeneric relationships remain insufficiently resolved. We combined detailed morphological examination with cytochrome c oxidase subunit I (COI) -based molecular analyses to provide an integrative taxonomic assessment of the genus. A total of 239 ticks representing ten species were collected from three zones of the Western Ghats, Kerala, India, with Haemaphysalis ( Kaiseriana ) spinigera Neumann, 1897 and Haemaphysalis ( Kaiseriana ) turturis Nuttall & Warburton, 1915 being the most abundant. Morphological identifications were confirmed by COI sequence analyses, generating 29 new sequences from 10 species, including five sequenced for the first time. These data were analysed together with publicly available sequences to infer phylogenetic relationships. Maximum Likelihood and Bayesian analyses produced largely congruent topologies but did not support the monophyly of most subgenera. Instead, the subgenus Allophysalis was recovered as sister to the remaining Haemaphysalis , with H. ( Allophysalis ) kopetdaghica Kerbabaev, 1962 forming an exception that may represent a distinct lineage requiring further taxonomic evaluation. Species delimitation analyses based on ASAP and PTP recovered 55 and 59 MOTUs, respectively, showing high congruence between methods. Inter-subgeneric divergence ranged from 12–19%, where most species exhibited less than 2% intraspecific variation, several taxa showed patterns consistent with cryptic diversity. Population genetic analyses of H. ( Kaiseriana ) bispinosa Neumann, 1897 revealed high within-population variation, moderate among-population differentiation, and 20 geographically structured haplotypes across 10 countries. Overall, our results support the utility of COI for Haemaphysalis identification at the species level and highlight the need for broader integrative approaches to resolve persistent taxonomic uncertainties in this medically important genus.